Application of directly observed procedural skills in hospital infection training: a randomized controlled trial - Zhumin Hu; Weipeng Zhang; Minyan Huang; Xiaoyan Liu (Frontiers in Medicine)
ObjectiveTo evaluate the effectiveness of the Direct Observation of Procedural Skills (DOPS) method in enhancing hospital infection training.MethodsA total of 196 infection control staff from clinical departments were selected from a hospital and divided into a control group and an experimental group. The control group received conventional hospital infection control, which training included 10 h of theory lectures and 5 h of practical demonstrations, while the experimental group received three formative assessments using the DOPS method in addition to the conventional training at two-month intervals. The results of the three DOPS assessments in the experimental group were analyzed and compared. The training effectiveness was further evaluated by comparing theory test scores and satisfaction ratings between the two groups.ResultsAmong these 196 study subjects, the majority were over 35 years old, female, doctors or nurses, with middle titles, a bachelor’s degree, and over 10 years of working seniority. The scores of using protective equipment and the handling of emergencies increased over the three DOPS evaluations (3.93 vs. 3.94 vs. 4.15 and 2.37 vs. 2.53 vs. 2.68, respectively). After adjusting for all covariates, the overall theoretical knowledge score in the experimental group was 7.968 times higher than that of the control group. The number of participants in the experimental group who were satisfied with the training was 86 compared to 71 in the control group for knowledge retention, 82 vs. 62 for clinical application, 83 vs. 67 for knowledge extrapolation, 88 vs. 73 for training methods, and 89 vs. 59 for motivation.ConclusionHospital infection control skills are important for clinical procedural skills. This study found that the application of the DOPS method in infection control training improved trainees’ practical skills, knowledge retention, and ability to implement infection control measures effectively in clinical settings. These results highlight the value of DOPS as a targeted intervention to enhance infection control training outcomes, supporting its further promotion in clinical education programs.